The winner's crime - Rutkoski, Marie (Rutkoski, Marie. Winner's trilogy, 2015)
The engagement of Lady Kestrel to Valoria's crown prince is the event of a lifetime, but to Kestrel it means living in a cage of her own making, so as she aches to tell the truth about her engagement, she becomes a skilled practitioner of deceit and as a spy passes information and gets close to uncovering a shocking secret.